Measuring intangible assets : A review of the state of the art - Van Criekingen, Kristof; Bloch, Carter; Eklund, Carita (Wiley, 2022)
This paper presents an overview of the state of the art in the field surrounding the measurement of “intangibles” for productivity analysis. The purpose of the paper is to inform indicator development and implementation in economic analysis, both at the micro and aggregated levels. The review seeks to capture the development of intangibles measurement, which has explored a variety of directions, both in terms of definition, method and data. We characterize both the diversity of the field and its development over time. Current national and firm level accounting rules lead, from an economic viewpoint on intangibles, to both an underestimation of intangible assets and productivity growth. Further work is needed, both concerning the estimation of “technical” aspects such as depreciation rates and deflators, and in the continued testing and comparison of different measurement efforts. Many opportunities exist to aggregate across or cross-validate between the measures that are currently being used, enhancing our understanding of the properties of these measures. Even though micro-based work faces great challenges in terms of data availability, it will be important for the estimation of depreciation rates and in developing our understanding (and thereby better measurement) of broader forms of intangibles, which can thereafter inform measurement at more aggregated levels.
Keywords: intangibles; literature review; measurement; fi=Taloustiede|en=Economics|